2020
DOI: 10.21203/rs.3.rs-42230/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute acalculous cholecystitis on a COVID-19 patient: a case report

Abstract: Background coronavirus disease-19 (COVID-19) has spread to several countries around the world and has become an unprecedented pandemic. We report an extremely rare case of acute acalculous cholecystitis on a COVID-19 patient. In our knowledge, this is the first report of laparoscopic cholecystectomy performed on a COVID-19 patient. Case presentation: a COVID-19 patient was diagnosed with acute acalculous cholecystitis and a multidisciplinary team decided to perform a percutaneous transhepatic biliary drainag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of included trials were presented in Table 1 . A total of 269 patients from 47 studies [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] were included in our meta-analysis. The mean age of operative patients with COVID-19 was 50.91 [95% CI, 42.49; 59.34], and 49% [95% CI, 0.33, 0.65] patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…Acalculous cholecystitis has been reported previously after an acute infection with Epstein Barr virus (EBV) [8]. Also, a case of acute acalculous cholecystitis has been reported in a COVID-19 patient but with no pathogen identi cation [9]. Our case represents an acute acalculous cholecystitis possibly associated with COVID-19, and the causative organism was identi ed as Candida albicans.…”
Section: Discussionmentioning
confidence: 78%
“…We encountered 7 case reports published about Covid-19 suspects or infected patients who underwent laparoscopic procedures (appendicectomy, cholecystectomy, perforated ulcer repair, internal hernia repair) [43][44][45][46][47][48][49]. The RT-PCR did not evidence the presence of viral ARN in peritoneal lavage, but, when tested it was present in stools +/− digestive wall in 50% of them.…”
Section: Clinical Evidences Regarding Laparoscopy In Covid-19 Positivmentioning
confidence: 94%
“…Mattone et al [49] reported a case of gangrenous acalculous cholecystitis in a patient hospitalized for COVID-19 pneumonia for 43 days in ICU. He followed the protocol, tempting a less invasive approach, percutaneous drainage, than followed by laparoscopic cholecystectomy.…”
Section: Clinical Evidences Regarding Laparoscopy In Covid-19 Positivmentioning
confidence: 99%